2016
DOI: 10.4103/1793-5482.145068
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intracerebellar hemorrhage secondary to lumboperitoneal shunt insertion

Abstract: Aim of this paper is to present and discuss a case of a delayed cerebellar parenchymal hemorrhage developing after L/P shunt placement with a NPH patient. A hypertensive patient admitted to our clinic with a diagnosis of NPH. The patient was placed a pressure adjustable L/P shunt without any surgical complication. He was discharged with an uneventful period. The patient was admitted to the emergency clinic of our hospital with a 1.5 × 1.5 cm diameter hematoma at the left cerebellar hemisphere on 2 days after h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, the HR for hemorrhagic stroke was lower in the LPS group than in the VPS group, although the difference was nonsignificant. The LPS procedure might be simpler because it is more minimally invasive and does not require ventricular puncture, although it still has the risk of over-drainage [15,29,30]. In addition, mortality was lower in the LPS group than in the VPS group (P < 0.05), which can be attributed to improved iNPH symptoms, safer procedures, fewer adverse effects, and overall lower HRs for MACEs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HR for hemorrhagic stroke was lower in the LPS group than in the VPS group, although the difference was nonsignificant. The LPS procedure might be simpler because it is more minimally invasive and does not require ventricular puncture, although it still has the risk of over-drainage [15,29,30]. In addition, mortality was lower in the LPS group than in the VPS group (P < 0.05), which can be attributed to improved iNPH symptoms, safer procedures, fewer adverse effects, and overall lower HRs for MACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Ventriculoperitoneal (VP) and lumboperitoneal (LP) shunt operations have no differences in clinical outcomes in the treatment of normal pressure hydrocephalus (NPH). 1 Compared to VP shunt operation, performing LP shunt operation is easier with a shorter operative time; 2 furthermore, it is minimally invasive, which enhances its efficiency in the treatment of NPH. Jia et al reported asuccess rate of 91.40% with LP shunting; only 5.85% of the cases were complicated by shunt tube malfunction, which mainly occurred in the peritoneal tube.…”
Section: Introductionmentioning
confidence: 99%
“…In 2 cases, conservative treatment was applied without any intervention (10,14). One of them died and the GOS score of the other was 5.…”
Section: Treatment Modalitiesmentioning
confidence: 99%